Designing Language Assessments in Context: Theoretical, Technical, and Institutional Considerations - Frank Giraldo (Asociación Colombiana de Profesores de Ingles, 2019)
The purpose of this article of reflection is to raise awareness of how poor design of language assessments may have detrimental effects, if crucial qualities and technicalities of test design are not met. The article first discusses these central qualities for useful language assessments. Then, guidelines for creating listening assessments, as an example, are presented to illustrate the level of complexity in test design and to offer a point of reference to evaluate a sample assessment. Finally, the article presents a discussion on how institutional school policies in Colombia can influence language assessment. The article concludes by highlighting how language assessments should respond to theoretical, technical, and contextual guidelines for them to be useful.